Scalable uncertainty management : 9th International Conference, SUM 2015, Quebec City, QC, Canada, September 16-18, 2015, proceedings /: 9th International Conference, SUM 2015, Quebec City, QC, Canada, September 16-18, 2015, proceedings. (2015) - Unknown
No abstract available